THE INTERACTIVITY OF THE TEACHING PROCESS: THE EFFECT OF DEMOGRAPHIC VARIABLES - Jovičić Vuković, Ana Đ.; Vukadinović, Maja; Papić-Blagojević, Nataša (International Journal of Economic Practice and Policy, 2024)
This research aimed to explore students’ evaluations of interactivity in the teaching process on a sample of 361 students. Demographic variables included questions related to gender, year of study, model of financing (budget/ self-financing), a place where they live (village/city), previous education and the higher education institution they attend. Participants had to evaluate their experience on the Likert scale of how interactivity is attributed to the teaching process they participated in. Results have shown that the overall assessment of interactivity is relatively high (M= 3.98, SD=.850). Furthermore, there is a significant effect of higher education institutions that students attend on their evaluations of interactivity (F(4, 360) = 3.187, p<.014). Results are discussed in the context of possible improvement of interactivity in the teaching process. Keywords: interactivity, teaching process, students’ assessments, higher education institutions